Development of microsystems for point-of-use microorganism detection - Wang, Lei, author; Dandy, David S., advisor; Tobet, Stuart A., committee member; Henry, Chuck S., committee member; Geiss, Brian J., committee member; Bailey, Travis S., committee member; Marchese, Anthony J., committee member (Colorado State University. Libraries, 2018)
To view the abstract, please see the full text of the document.
Keywords: biosensors; inertial focusing; antibody sensor; microfluidics; DNA sensor